Revis??o taxon??mica e sistem??tica filogen??tica de Phrynops geoffroanus (Schweigger, 1812) (Testudines: chelidae) - Carvalho, Vin??cius Tadeu de (2018)
Submitted by Divis??o de Documenta????o/BC Biblioteca Central (ddbc@ufam.edu.br) on 2018-01-25T15:47:23Z No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) Reprodu????o N??o Autorizada.pdf: 47716 bytes, checksum: 0353d988c60b584cfc9978721c498a11 (MD5)